Fas Signaling in Dendritic Cells Mediates Th2 Polarization in HDM-Induced Allergic Pulmonary Inflammation - Han, Miaomiao; Hu, Ran; Ma, Jingyu; Zhang, Baohua; Chen, Ce; Li, Huabin; Yang, Jun; Huang, Gonghua (Frontiers in Immunology, 2018)
Fas-Fas ligand (FasL) signaling plays an important role in the development of allergic inflammation, but the cellular and molecular mechanisms are still not well known. By using the bone marrow-derived dendritic cell (BMDC) transfer-induced pulmonary inflammation model, we found that house dust mite (HDM)-stimulated FAS-deficient BMDCs induced higher Th2-mediated allergic inflammation, associated with increased mucus production and eosinophilic inflammation. Moreover, FAS-deficient BMDCs promoted Th2 cell differentiation upon HDM stimulation in vitro. Compared to wild-type BMDCs, the Fas-deficient BMDCs had increased ERK activity and decreased IL-12 production upon HDM stimulation. Inhibition of ERK activity could largely increase IL-12 production, consequently restored the increased Th2 cytokine expression of OT-II CD4+ T cells activated by Fas-deficient BMDCs. Thus, our results uncover an important role of DC-specific Fas signaling in Th2 differentiation and allergic inflammation, and modulation of Fas signaling in DCs may offer a useful strategy for the treatment of allergic inflammatory diseases.